Functional analysis of Csk in signal transduction through the B-cell antigen receptor. - Hata, A (1994)
In B cells, two classes of protein tyrosine kinases (PTKs), the Src family of PTKs (Lyn, Fyn, Lck, and Blk) and non-Src family of PTKs (Syk), are known to be involved in signal transduction induced by the stimulation of the B-cell antigen receptor (BCR). Previous studies using Lyn-negative chicken B-cell clones revealed that Lyn is necessary for transduction of signals through the BCR. The kinase activity of the Src family of PTKs is negatively regulated by phosphorylation at the C-terminal tyrosine residue, and the PTK Csk has been demonstrated to phosphorylate this C-terminal residue of the Src family of PTKs. To investigate the role of Csk in BCR signaling, Csk-negative chicken B-cell clones were generated. In these Csk-negative cells, Lyn became constitutively active and highly phosphorylated at the autophosphorylation site, indicating that Csk is necessary to sustain Lyn in an inactive state. Since the C-terminal tyrosine phosphorylation of Lyn is barely detectable in the unstimulated, wild-type B cells, our data suggest that the activities of Csk and a certain protein tyrosine phosphatase(s) are balanced to maintain Lyn at a hypophosphorylated and inactive state. Moreover, we show that the kinase activity of Syk was also constitutively activated in Csk-negative cells. The degree of activation of both the Lyn and Syk kinases in Csk-negative cells was comparable to that observed in wild-type cells after BCR stimulation. However, BCR stimulation was still necessary in Csk-negative cells to elicit tyrosine phosphorylation of cellular proteins, as well as calcium mobilization and inositol 1,4,5-trisphosphate generation. These results suggest that not only activation of the Lyn and Syk kinases but also additional signals induced by the cross-linking of the BCR are required for full transduction of BCR signaling.